G6PC3 Deficiency: Primary Immune Deficiency Beyond Just Neutropenia - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Glucose-6-phosphatase catalytic subunit 3 (G6PC3) deficiency was recently defined as a new severe congenital neutropenia subgroup remarkable with congenital heart defects, urogenital malformations, endocrine abnormalities, and prominent superficial veins. Here, we report 3 patients with G6PC3 deficiency presenting with recurrent diarrhea, failure to thrive, and sinopulmonary infections leading to bronchiectasis. In patient I and II, a combined immune deficiency was suspected due to early-onset disease with lymphopenia, neutropenia, and thrombocytopenia, along with variable reductions in lymphocyte subpopulations and favorable response to intravenous -globulin therapy. Apart from neutropenia, all 3 patients had intermittent thrombocytopenia, anemia, and lymphopenia. All patients had failure to thrive and some of the classic syndromic features of G6PC3 deficiency, including cardiac abnormalities and visibility of superficial veins in all, endocrinologic problems in PI and PIII, and urogenital abnormalities in PII. Our experience suggests that a diagnosis of congenital neutropenia due to G6PC3 may not be as straightforward in such patients with combined lymphopenia and thrombocytopenia. A high index of suspicion and the other syndromic features of G6PC3 were clues to diagnosis. Screening of all combined immune deficiencies with neutropenia may help to uncover the whole spectra of G6PC3 deficiency.
Keywords: severe congenital neutropenia; inflammatory bowel disease; combined immune deficiency; intravenous gamma-globulin; SEVERE CONGENITAL NEUTROPENIA; SYNDROMIC NEUTROPENIA; MUTATIONS; LEUKEMIA; OSTEOPOROSIS; SPECTRUM; TYPE-4; DEFECT; RISK